The stories we tell : a novel - Henry, Patti Callahan (St. Martin's Press, 2014)
"Eve and Teddy Morrison are Savannah's power couple. They're on every artistic board and involved deeply in the community. And they have the wealth and name that comes from being part of an old Savannah family. But things aren't as good as they look: Eve and Teddy are fighting about her work, their marriage, and their daughter most of all"--